Development of clinical care guidelines for faculty and residents in the era of COVID‐19. Issue 7 (6th May 2020) - Park, Jason S.; El‐Sayed, Ivan H.; Young, VyVy N.; Pletcher, Steven D.
Abstract: Background: The global COVID‐19 pandemic brings new challenges to otolaryngology resident education. Surgical volume and clinic visits are curtailed, personal protective equipment for operating room participation is restricted, and the risk of COVID‐19 disease transmission during heretofore routine patient care is the new norm. Methods: We describe a small‐team "cohorting" protocol including guidelines for faculty and resident in common clinical scenarios with attention paid to the risk of common otolaryngologic procedures. Results: A rotating small‐team approach was implemented at each clinical site, limiting interaction between department members but providing comprehensive coverage. Faculty were involved at the earliest phase of clinical interactions. Guidelines delineated faculty and resident roles based on risk stratification by patient COVID status and anticipated procedures. Special consideration was given to high‐risk procedures such as endoscopy and tracheotomy. Conclusions: A small‐team‐based approach with guidelines for faculty/resident roles may mitigate risk while optimizing patient care and maximizing education.